2003
DOI: 10.1086/374565
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Telomerase Reverse Transcriptase Gene and Haploinsufficiency of Telomere Maintenance in Cri du Chat Syndrome

Abstract: Cri du chat syndrome (CdCS) results from loss of the distal portion of chromosome 5p, where the telomerase reverse transcriptase (hTERT) gene is localized (5p15.33). hTERT is the rate-limiting component for telomerase activity that is essential for telomere-length maintenance and sustained cell proliferation. Here, we show that a concomitant deletion of the hTERT allele occurs in all 10 patients with CdCS whom we examined. Induction of hTERT mRNA in proliferating lymphocytes derived from five of seven patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 42 publications
0
41
0
3
Order By: Relevance
“…2, although harboring much stronger telomere signals than their adjacent normal cells, lacked detectable hTERT protein, suggesting the activation of an alternative mechanism for telomere lengthening (Figure 3). Telomere hybridization was performed, and the maximum intensity projections of the acquired images were analysed using the IMP image-processing software (the Center for Image Analysis at Uppsala University, Uppsala, Sweden) (Zhang et al, 2003). Telomere signals in 10 nuclei from normal or different pathological regions were measured separately, and then normalized by DAPI fluorescence intensity in corresponding areas as described van Heek et al, 2002).…”
Section: Telomere Attrition In Cervical Carcinogenesismentioning
confidence: 99%
“…2, although harboring much stronger telomere signals than their adjacent normal cells, lacked detectable hTERT protein, suggesting the activation of an alternative mechanism for telomere lengthening (Figure 3). Telomere hybridization was performed, and the maximum intensity projections of the acquired images were analysed using the IMP image-processing software (the Center for Image Analysis at Uppsala University, Uppsala, Sweden) (Zhang et al, 2003). Telomere signals in 10 nuclei from normal or different pathological regions were measured separately, and then normalized by DAPI fluorescence intensity in corresponding areas as described van Heek et al, 2002).…”
Section: Telomere Attrition In Cervical Carcinogenesismentioning
confidence: 99%
“…Monosomy for a contiguous stretch of genes at the distal portion of chromosome 5p is associated with CdCS. Several genes in the region including SEMA5A, CTNND2, and TERT are of particular interest because their products play major roles during embryonic and neuronal development [Simmons et al, 1998;Medina et al, 2000;Zhang et al, 2003]. The SEMA5A gene encodes a membrane protein with a semaphorin domain and several thrombospondin type-1 repeats, and acts as a signaling molecule that regulates axonal guidance and neuronal migration during development.…”
Section: Discussionmentioning
confidence: 99%
“…The telomerase reverse transcriptase (TERT) gene is localized at 5p15.33 and encodes the rate-limiting component of telomerase complex essential for telomere length maintenance and sustained cell proliferation [Zhang et al, 2003]. It has been demonstrated that individuals with CdCS who are haploinsufficient for TERT have shorter telomere length compared to age-matched unaffected individuals [Zhang et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the corresponding region (Rp11-79L17) was conserved in patient 3, this gene might be essential for mental conditions. Zhang et al (2003) reported that the deletion of the hTERT gene located on 5p15.33 in 5p-syndrome might impair normal fetal development. However, we have shown that patients 1, 4, and 5, who lacked IUGR, as well as those with IUGR, lost hTERT.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%